Factors motivating students with disabilities to access and participate in university education in Ghana. Issue 2 (17th February 2023) - Akoto, Yaw; Nketsia, William; Opoku, Maxwell Peprah; Opoku, Emmanuel Kofi
ABSTRACT: Education has been described as a 'bridging right' that empowers persons with disabilities to justifiably lay claim to other rights, such as the right to work, the right to participate in politics, etc. While much research has reported on the challenges encountered by persons with disabilities in higher education, very little is known about the factors that enhance their retention and continuous participation in higher education in Ghana. The objective of this study was therefore to explore the factors that influence students with disabilities to access and participate in higher education. Using Maslow's hierarchy of needs, qualitative semi-structured interviews were conducted with individuals with disabilities: physical disability ( n  = 8) and visual impairment ( n  = 3), who were recruited from one of the largest higher education institutions in Ghana. The results from the thematic analysis indicate that the participants were motivated more by the higher-level needs of Maslow's pyramid, that is, safety, self-esteem and transcendence, than the lower-level needs. The study limitations, recommendations for future research and policy implications are also discussed.